The Impact of Modern Marketing within Administrative Facilities in Kingdom of Sudia Arabia (International Journal of Financial, Administrative and Economic Sciences, 2024)
In the face of rapid technological advancements, modern marketing has become a crucial factor in the development of organizational management strategies. This study explores the impact of modern marketing strategies on the performance of administrative organizations in Saudi Arabia, with a particular focus on digital marketing, social media marketing, and data analytics. With the widespread adoption of digital technology and the increasing use of the internet and social media, Saudi Arabia has witnessed a notable shift in marketing practices. It has become essential for administrative organizations in the kingdom to adopt marketing strategies that align with these developments to achieve success and growth. The research aimed to analyze how digital marketing and social media strategies impact administrative performance in organizations, as well as to explore the role of data analytics in improving marketing strategies and decision-making. This was achieved by examining the effects of these tools on operational efficiency, customer engagement, and strategic decision-making. The study employed a mixed-method approach combining both qualitative and quantitative techniques. Surveys and interviews with marketing managers in administrative organizations were used to gather accurate data on the impact of modern marketing strategies. Additionally, secondary data from previous reports and research were analyzed. The study's findings indicated that digital marketing plays a significant role in enhancing operational efficiency. Tools such as email marketing and search engine marketing contribute to increased customer engagement and more effective achievement of marketing goals. Furthermore, social media marketing campaigns were found to be effective in building brand awareness and strengthening customer interactions, which enhances organizational reputation. Data analytics was also shown to assist organizations in making more informed decisions by providing accurate insights into customer behavior and market trends. The research recommends that administrative organizations enhance their digital marketing strategies and invest more in social media marketing to improve customer communication effectiveness. Additionally, it is advised to leverage data analytics techniques to refine marketing strategies and anticipate future changes. The study indicates that modern marketing has a significant impact on improving the performance of administrative organizations in Saudi Arabia. By adapting to modern tools and technologies, organizations can boost their competitive edge and achieve positive outcomes in a changing business environment.
Keywords: Modern Marketing; Digital Marketing; Social Media Marketing; Data Analytics; Administrative Organizations; Saudi Arabia